Investigate The Combination Of Coconut Shell And Grained Palm Kernel To Replace Aggregate In Concrete: A Technical Review - Siti Aminah, Tukiman; Sabarudin, Mohd (2009)

(untitled)
Conventional coarse aggregate namely gravel and fine aggregate is sand in concrete will be used as control. While natural material is coconut shell as course aggregate and grained palm kernel as fine aggregate will be investigate to replace the aggregate in concrete. In this studies, five different concrete mixes with different the combination of natural material content namely 0%,25%,50%,75% and 100%.Three sample specimen will be prepared for each concrete mixes. The parameters will be tested are flexural strength, compressive strength, tensile strength, modulus of elasticity, durability and deflection crack behavior. The effect of using different length of natural material aggregate will also investigate. The effect of aggregate content to workability will also examine. The expected outcome of the study is the combination of coconut shell and grained palm kernel shell has potential as lightweight aggregate in concrete. Also, using the combination of coconut shell and grained palm kernel as aggregate in concrete can reduce the material cost in construction because of the low cost and abundant agricultural waste.